2012
DOI: 10.1371/journal.pone.0031533
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Murine Leukemia Retroviral Integration and Structure Fluctuation of Target DNA

Abstract: Integration of the retroviral genome into host DNA is a critical step in the life cycle of a retrovirus. Although assays for in vitro integration have been developed, the actual DNA sequences targeted by murine leukemia retrovirus (MLV) during in vitro reproduction are unknown. While previous studies used artificial target sequences, we developed an assay using target DNA sequences from common MLV integration sites in Stat5a and c-myc in the genome of murine lymphomas and successfully integrated MLV into the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 25 publications
(34 reference statements)
0
7
0
Order By: Relevance
“…In the current study, we modified the protocol further by omitting the PCR reaction and using the actual human CD27 gene as the target DNA sequence (Fig. 1B) [7], [11].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the current study, we modified the protocol further by omitting the PCR reaction and using the actual human CD27 gene as the target DNA sequence (Fig. 1B) [7], [11].…”
Section: Resultsmentioning
confidence: 99%
“…The details of target sequence and the replacement nucleotides were represented in text. The percentage of integration was estimated by determining the copy number of the products of integration into the target DNA compared to the copy number of the products of integration into the whole-sequence DNA (i.e., the target DNA plus the plasmid), according to previously reported methods [7], [9], [11]. First, the number of E. coli colonies exhibiting integration into the target segment was determined.…”
Section: Methodsmentioning
confidence: 99%
“…They often coincide with other, comparably simpler structures, such as cruciform, hairpins, H and Z-DNA, all of which we found abundantly at the hGR and nhGR BPs. The preponderance of nhGR BPs to adopt cruciform structures is not surprising in the light that they are preferred targets for retroviral integration into host genomes via nonhomologous recombination [Katz et al, 1998;Tsuruyama et al, 2012], and have been implicated as the likely source for single and double strand breaks in the genome [Bacolla et al, 2004]. Finally, the value and usefulness of novel data and hypotheses often derive from the accuracy of their predictions.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that the terminal ends of the dsDNA might be critical for integration, and that the presence of a dinucleotide capsid at the terminal 3′-ends is particularly essential. 13 , 41 Subsequently, the free energy change released from the broken phosphodiester bonds in the host dsDNA promotes the formation of new bonds joining the viral DNA ends to the ends of cleaved host DNA. DNA synthesis extends from the host DNA flanking the host-viral DNA junctions and fills in the gaps adjacent to the viral DNA, displacing the viral DNA ends.…”
Section: Retroviral Genome Integration Into the Host Genomementioning
confidence: 99%
“… 9 , 10 DNA secondary structural fluctuation around an integration hotspot might contribute to the open chromatin structure in the transcriptionally active site that would likely promote proviral integration after the physical breakage of the double-stranded DNA (dsDNA). 13 , 14 …”
Section: Introductionmentioning
confidence: 99%